"I literally had no support": barriers and facilitators to supporting the psychosocial wellbeing of young people with mental illness in Tasmania, Australia - Melissa Savaglio; Marie B. H. Yap; Toni Smith; Ash Vincent; Helen Skouteris (BMC, 2023)
Abstract Background There has been limited focus on understanding the barriers and facilitators to meeting the broader psychosocial needs of young people with mental illness from the perspectives of young people. This is required to advance the local evidence base and inform service design and development. The aim of this qualitative study was to explore young people's (10-25 years) and carers' experiences of mental health services, focusing on barriers and facilitators to services supporting young people's psychosocial functioning. Methods This study was conducted throughout 2022 in Tasmania, Australia. Young people with lived experience of mental illness were involved in all stages of this research. Semi-structured interviews were conducted with 32 young people aged 10-25 years with experience of mental illness, and 29 carers (n = 12 parent-child dyads). Qualitative analysis was guided by the Social-Ecological Framework to identify barriers and facilitators at the individual (young person/carer level), interpersonal, and service/systemic level. Results Young people and carers identified eight barriers and six facilitators across the various levels of the Social-Ecological Framework. Barriers included, at the individual level: (1) the complexity of young people's psychosocial needs and (2) lack of awareness/knowledge of services available; at the interpersonal level: (3) negative experiences with adults and (4) fragmented communication between services and family; and at the systemic level: (5) lack of services; (6) long waiting periods; (7) limited service accessibility; and (8) the missing middle. Facilitators included, at the individual level: (1) education for carers; at the interpersonal level: (2) positive therapeutic relationships and (3) carer advocacy/support; and at the systemic level: (4) flexible or responsive services, (5) services that address the psychosocial factors; and (6) safe service environments. Conclusions This study identified key barriers and facilitators to accessing and utilising mental health services that may inform service design, development, policy and practice. To enhance their psychosocial functioning, young people and carers want lived-experience workers to provide practical wrap-around support, and mental health services that integrate health and social care, and are flexible, responsive and safe. These findings will inform the co-design of a community-based psychosocial service to support young people experiencing severe mental illness.